Introducing activities of the Archives of Infectious Diseases History (AIDH) project: Historical epidemiology - Wataru Iijima; Hiroki Inoue; Tomoo Ichikawa (Tropical Medicine and Health, 2021)
Abstract The AIDH is a project as a historical epidemiology. The AIDH aims to collect, maintain, and manage past epidemiological materials and to offer these materials to persons who are interested in the history and in the fields of tropical medicine and global health. In this paper, we introduce our purpose and activities and show a hypothesis about lymphatic filariasis with Brugia malayi in Japan as a case of historical epidemiology. We hope to build fruitful ties between historians and scholars of tropical medicine and global health workers through an interdisciplinary approach to the history of control of infectious diseases.